Breaking the Chain of Figure Sacralization and Power Relations to Protect Students from Sexual Violence - Najmudin (JURNAL ILMIAH GEMA PERENCANA, 2026)
Sexual violence in religious educational institutions has reached an alarming level of emergency, threatening the safety of students and tarnishing the institution's integrity due to protection gaps within the social structures and organizational doctrines. The urgency of this issue lies in the "iceberg phenomenon," where the sacralization of leading figures and power relation imbalances create dark spaces that perpetuate exploitative actions without adequate oversight. The policy analysis methodology employed in this paper is a descriptive qualitative approach, utilizing problem prioritization instruments through the Urgency, Seriousness, and Growth (USG) method, alongside root cause analysis using a fishbone diagram. The evaluation of policy alternatives was conducted by adopting William N. Dunn’s criteria, which include effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The analysis results indicate that a culture of absolute obedience and the characteristics of a total institution are determinant factors that obstruct transparency and accountability. The discussion emphasizes that the transformation from charismatic authority to professional authority subject to the law is an absolute prerequisite for breaking the cycle of violence. As strategic recommendations, this policy promotes the digitalization of anonymous complaint channels, the reform of accreditation indicators based on risk mitigation, and the formalization of external oversight boards. The implementation of these steps is urgently required for immediate execution by policymakers to deconstruct the sacralization of figures into accountable leadership, thereby guaranteeing the right of every student to learn in a safe and transparent environment in accordance with constitutional mandates and prevailing child protection regulations in Indonesia